Australia is Facing a Housing Affordability Crisis: Is the Solution to this Problem the Singapore Model of Housing? - John McLaren; Allan Yeo; Michael Sweet (Australasian Accounting, Business and Finance Journal, 2017)
Australia is pricing young buyers out of the housing market. Unfortunately, debt-free home ownership in the retirement years is a key part of the Australian welfare system. This paper provides one possible solution to the current housing predicament of Australia. In doing so, the paper examines the housing strategy in Singapore, where residents are provided with accommodation at a reasonable cost. This strategy is examined and translated for use in Australia. In conclusion the paper proposes that the Singapore model of home ownership is worthy of consideration by the government of Australia.
Keywords: Housing crisis; Australia; Singapore; Superannuation; housing affordability